Dr. Francisco Magno was formally honored as a Robert S. McNamara awardee - Magno, Francisco A. (Animo Repository, 1999)
Political Science faculty and SDRC director Dr. Francisco Magno was formally honored as a Robert S. McNamara Awardee in Washington, D.C. The McNamara Fellowship Program was established in 1982 by the World Bank. His winning research proposal was "Localizing Social Development, Mobilizing Social Capital: Participation and Poverty Reduction in the Southern Philippines".